Two novel variants of uncertain significance in GP9 associated with Bernard–Soulier syndrome: Are they true mutations?. (3rd April 2018) - Boisseau, P.; Debord, C.; Eveillard, M.; Quéméner, A.; Sigaud, M.; Giraud, M.; Talarmain, P.; Thomas, C.; Landeau, G.; Bezieau, S.; Petesch, B. Pan; Béné, M. C.; et al.
Abstract: Bernard–Soulier syndrome (BSS) is an autosomal recessive major thrombocytopathy, the symptoms of which are mainly marked by mucocutaneous bleeding. This rare disease, initially described in the 1970s, is the result of an abnormal formation of the glycoprotein complex Ib-IX-V (GP Ib-IX-V), a platelet receptor of von Willebrand factor. A large number of mutations, sometimes involving the GP9 gene, have been described as possibly responsible for the disease. We report here the case of a BSS patient who presented with persistent thrombocytopenia (31x10 9 /L) and decreased surface expression of GPIb-IX-V on large platelets with anisocytosis. Thorough molecular analyses disclosed two previously unreported GP9 variants, respectively c.230T>A (p.Leu77Gln) and c.255C>A (p.Asn85Lys). Both are likely to modify the conformation of GP-IX interactions with other glycoproteins of the Ib-IX-V complex and thus proper expression of this complex on the membrane of platelets.